Influence of defects of nanostructured ZnO films on the photovoltaic characteristics of perovskite solar cells - Afanasyev, D.A.; Mirzoev, K.Yu.; Ibrayev, N.Kh. (IOP publishing LTD, 2018)
The influence of the defects in ZnO films on the electrical and photovoltaic properties of perovskite solar cells was investigated in the work. According to the results of the research it was established that the defects in ZnO films affects the concentration of defects of perovskite films synthesized on the ZnO surface. However, the difference in the defect concentration in perovskite films is about 30%, while the concentration of defects in ZnO differs by 1000 times. A less significant influence is the concentration of ZnO defects on the electrical and photovoltaic properties of perovskite solar cells. The magnitude of the shortcircuit photocurrent and the open voltage of the cells are affected by the concentration of perovskite defects and the quality of the perovskite-ZnO interface.